SOSIALISASI METODE PEMBUATAN MP-ASI - Philipus, Vitta Margareth (Gapenas Publisher, 2023)
The problem of disorders in the growth and development of infants under two years old is a problem that needs to be addressed seriously. This problem is caused by the age of infants under two years old being a critical period in the process of infant growth and development both in terms of intelligence and physical. This is because the age of two years old is a critical period in the process of child growth and development both physically and intellectually. MPASI is food or drink containing nutrients, given to infants or children aged 6-24 months, and given gradually according to the age and digestive ability of the infant in order to meet nutritional needs, in addition to breast milk. There are still toddlers with malnutrition and BGM. The incidence of malnutrition is still high, which is around 20.2% of the total number of infants. This activity aims to increase knowledge and provide education about Providing MP-ASI to Mothers Who Have Children Aged 6-24 Months. The community service activity was held on Wednesday, January 15, 2024 at 09.30 WIB, the location of the implementation was at the Singandaru Health Center. The participants who attended were 16 mothers who had children aged 6-24 Months. Based on the results of the activity, there was an increase in the knowledge of mothers who have children aged 6-24 months in making MP-ASI. It is hoped that mothers will be able to independently make more varied and healthy MP-ASI and in the future they can independently process and market MP-ASI products